Does Hepatitis B Infection Or Son Preference Explain The Bulk of Gender Imbalance In China? - Das Gupta, Monica, 1975- 1975- (The World Bank, 2008)
China has a large deficit of females, and public policies have sought to reduce the son preference that is widely believed to cause this. Recently a study has suggested that up to 75 percent of this deficit is attributable to hepatitis B infection, indicating that immunization programs should form the first plank of policy interventions. However, a large medical dataset from Taiwan (China) shows that hepatitis B infection raises women's probability of having a son by only 0.25 percent. And demographic data from China show that the only group of women who have elevated probabilities of bearing a son are those who have already borne daughters. This pattern makes it difficult to see how any biological factor can explain a large part of the imbalance in China's sex ratios at birth -- unless it can be shown that it somehow selectively affects those who have borne girls, or causes them to first bear girls and then boys. The Taiwanese data suggest that this is not the case with hepatitis B, since its impact is unaffected by the sex composition of previous births. The data support the cultural, rather than the biological, explanation for the "missing women